Trypanotolerant N'Dama and West African Shorthorn cattle - Trail, J.C.M. (Westview Press, Inc., 1984)
Discusses the characteristics of trypanotolerant West African Shorthorn and N'dama cattle, examining their productivity, mechanisms of trypanotolerance and environmental factors affecting trypanotolerance, esp. level of tsetse challenge and previous exposure.